Computer-assisted drug repurposing for thymidylate kinase drug target in monkeypox virus - Ajmal, Amar; Mahmood, Arif; Hayat, Chandni; Hakami, Mohammed Ageeli; Alotaibi, Bader S.; Umair, Muhammad; Abdalla, Ashraf N.; Li, Ping; He, Pei; Wadood, Abdul; Hu, Junjian (Frontiers in Cellular and Infection Microbiology, 2023)
Monkeypox is a zoonotic disease caused by brick-shaped enveloped monkeypox virus (MPXV) that belongs to the family of ancient viruses known as Poxviridae. Subsequently, the presence of this virus was reported in various countries. The virus is transmitted by respiratory droplets, skin lesions, and infected body fluids. The infected patients experience fluid-filled blisters, maculopapular rash, myalgia, and fever. Due to the lack of effective drugs or vaccines, there is a need to identify the most potent and effective drugs to reduce the spread of MPXV. The current study aimed to use computational methods to quickly identify potentially effective drugs against the monkeypox virus (MPXV). In our study, the monkeypox protein thymidylate kinase (A48R) was targeted because it is a unique drug target. We screened a library of 9000 FDA-approved compounds of the DrugBank database by using various in silico approaches such as molecular docking, and molecular dynamic (MD) simulation. Based on docking score and interaction analysis compounds DB12380, DB13276, DB13276, DB11740, DB14675, DB11978, DB08526, DB06573, DB15796, DB08223, DB11736, DB16250, and DB16335 were predicted as the most potent. To examine the dynamic behavior, and stability of the docked complexes three compounds DB16335, DB15796, and DB16250 along with the Apo state were simulated for 300ns. The results revealed that compound DB16335 revealed the best docking score (-9.57 kcal/mol) against the monkeypox protein thymidylate kinase. Additionally, during the 300 ns MD simulation period, thymidylate kinase-DB16335 showed great stability. Further, in vitro and in vivo study is recommended for the final predicted compounds.